Research on the Relationship Between Cross-Level Motivation, Integrated Emotion, and Virtual Knowledge Community Commitment - Sun, Bing; Mao, Hongying; Kang, Min (Frontiers in Psychology, 2021)
Community commitment is the key to the success of virtual communities. Under the background of virtual knowledge community, based on motivation hierarchy model and integrated emotion theory, this paper takes "motivation-emotion-community commitment" as the main framework, and introduces multiple mediation and regulation functions to establish the relationship model of motivation hierarchy, integrated emotions and community commitment. The results show that the user motivation follows the hierarchical structure of the layer-by-layer influence from the situational level to the personality level, that is, knowledge seeking motivation and entertainment seeking motivation at situational level will positively affect social interaction motivation at contextual level, thereby enhancing user self-efficacy at personality level. Users have abundant integrated emotions towards the virtual knowledge community, namely, satisfaction, attachment and identity, and such multi-integrated emotional model is more conducive to promoting users' community commitment. At the same time, attachment, identity and satisfaction have an interactive complement, that is, when satisfaction is low, attachment and identity will complement and strengthen community commitment.